Sol Plaatje's Native Life in South Africa : Past and present - Willan, Brian (Book collections on Project MUSE., 2018)
First published in 1916, Sol Plaatje's Native Life in South Africa was written by one of the South Africa's most talented early 20th-century black leaders and journalists. Plaatje's pioneering book arose out of an early African National Congress campaign to protest against the discriminatory 1913 Natives Land Act. Native Life vividly narrates Plaatje's investigative journeying into South Africa's rural heartlands to report on the effects of the Act and his involvement in the deputation to the British imperial government.